Kejadian Luar Biasa COVID-19, Sebuah Tinjauan Literatur Secara Singkat - zilhadia Zilhadia (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2020)
Abstract: The world of health is totally horrendous with a disease that attacks internal breathing and can cause death. The cause of this disease was identified as Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2) and the desease called Corona Virus Desease 2019 (COVID-19). For the first time in the last two decades, a disease has an impact on the ideology, politics, economics, social, culture, psychology, defense and security of a country, and occurs globally. COVID-19 is a zoonotic disease with a mortality rate of 6,9%. Person-to-person transmission can occur through droplets or direct contact. COVID-19 will be transmitted massively if infection control is delayed or there is no adequate personal protective equipment for health workers. Confirmation of patients who are positive for COVID-19 requires a relatively long time because it requires a careful examination of RT-PCR with a limited number of devices in Indonesia. At present, there is no definitive treatment for COVID-19 even though several drugs are being investigated. To immediately identify patients and prevent further spread, doctors must be aware of travel or contact history with patients who have symptoms of COVID-19. Abstrak: Dunia tiba tiba dihebohkan dengan adanya sebuah penyakit yang menyerang  pernafasan bagian dalam dan dapat menyebabkan kematian. Penyakit ini diberi nama Corona Virus Desease 2019 (COVID-19) yang disebabkan oleh  Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2). Untuk pertama kalinya sepanjang 2 dekade terakhir, sebuah penyakit berdampak terhadao  ideologi, politik, ekonomi, social, budaya,  psikologi, pertahanan dan keamanan suatu negara, dan terjadi secara global. COVID-19 adalah  penyakit zoonosis dengan tingkat kematian mencapai 6,9%. Penularan dari orang ke orang dapat terjadi melalui droplet atau kontak langsung. COVID-19 akan menular secara masif jika pengendalian infeksi  terlambat atau tidak ada alat pelindung diri yang memadai bagi petugas kesehatan. Konfirmasi pasien yang positif terkena COVID-19 membutuhkan waktu yang relatif lama karena  memerlukan pemeriksaan yang teliti yaitu RT-PCR dengan jumlah alat yang terbatas di Indonesia. Saat ini, tidak ada pengobatan yang pasti untuk COVID-19 meskipun beberapa obat sedang diselidiki. Untuk segera mengidentifikasi pasien dan mencegah penyebaran lebih lanjut, dokter harus mewaspadai perjalanan atau riwayat kontak dengan pasien yang mempunyai gejala COVID-19.